51‐4: QLED‐on‐Silicon Microdisplays. Issue 1 (25th September 2020) - Su, Sikai; Li, Chengling; Zhang, Min; Chen, Shuming; Zhang, Shengdong
Abstract : In this paper, a 0.47 inch active‐matrix microdisplay with top‐emitting monochromatic quantum dot light‐emitting diode (QLED) array on silicon is demonstrated. A titanium nitride (TiN) is employed as the anode and the devices are fabricated by all‐solution process. The driver chip is designed especially for QLED microdisplay. The demonstrated microdisplay exhibits a maximum brightness of 267 cd/m 2 and a gray level of 256.